Time Evolution of Dehydration‐Induced Stick‐Slip Behaviors of Simulated Bassanite Gouges - M. Kawabata; R. Shiraishi; J. Muto; H. Nagahama; Y. Sasaki; M. Iwasaki (Geophysical Research Letters)
Abstract Pore pressure by dehydrating hydrous minerals can trigger deep and intermediate‐depth earthquakes. We performed friction experiments on simulated bassanite gouges under various confining pressures and temperatures. At room temperature (RT), stress drops and recurrence intervals of stick‐slip events varied with confining pressures. Under a confining pressure of 200 MPa and 110°C, stress drops and recurrence intervals decreased over time. Microstructures indicate that gouges deformed under RT contain numerous Riedel shears. On the other hand, a sample deformed under the confining pressure of 200 MPa and 110°C had few Riedel shear planes. Above observations indicate that the elevated pore pressure by the dehydration of bassanite gouges reduces the effective pressures controlling slip behaviors and suppresses the development of shear planes. We derived time function of dehydration‐driven pore pressure evolution using Avrami kinetics, which can be expressed by the Weibull distribution function representing the failure probability. Our result shows that the kinetics‐driven pore fluid evolution controlled the stick‐slip behaviors of the bassanite gouges.